Adeptia BPM Server 4.1 more than enterprise application integration on steroids. - Maurer, Paul T. (SOA webservices journal.)
Adeptia has released the latest version of its BPM server. The Adeptia BPM server is another entry in the fast growing market for Business Process Management Tools